ESG strategy in the supply chain considering ownership structures - Jiayu Liu (Discover Sustainability)
Abstract Firms with higher ESG ratings typically exhibit greater efficiency in resource utilization, thereby promoting sustainable development. The ownership structure of a supply chain influences corporate behavior, affecting both overall performance and ESG information management practices. This paper employs a Stackelberg model to explore ESG information management strategies within supply chains characterized by different ownership structures, specifically comparing vertical and horizontal configurations. Our findings indicate that when retailers possess a dominant market position alongside a shareholding manufacturer, the incentive to enhance ESG information levels significantly increases as the shareholding ratio rises. Moreover, the held manufacturer shifts from a focus on price-based competition to quality-based competition. We establish a benchmark model, and our analysis demonstrates that, relative to the benchmark scenario, manufacturers in both ownership structures exhibit a stronger motivation to improve ESG information levels. Accordingly, manufacturers are advised to develop ESG information management strategies that are tailored to their specific ownership structure, shareholding ratio, and the investment cost coefficient associated with ESG information enhancements.